Conceptualization of the Continuous Quality Improvement Model in Islamic Education - Azza, Risma Latiful; Yasin, Muhammad (Institut Agama Islam Negeri Sorong, 2025)
Islamic education in Indonesia currently faces serious challenges in building a sustainable and contextual quality assurance system. The existing quality system tends only to emphasise the administrative aspect and does not fully reflect the core values in Islam, such as tauhid, amanah, ihsan, and deliberation. The quality approach adopted from the Western paradigm is also often irrelevant to Islamic educational institutions' spiritual and cultural needs. This research aims to conceptualize the Continuous Quality Improvement (CQI) model in Islamic education that is integrated with Islamic values. The method used is library research with a qualitative approach. Data was collected through searches of national and international scientific journals, academic books, and official documents related to quality management and Islamic education. The research results produced five main components in the Islamic-based CQI model: Islamic basic values, Islamic transformational leadership, sustainable quality culture, the PDCA cycle based on spiritual values, and the collective participation of all institutional components. This model can bridge the gap between modern quality theory and the reality of Islamic education, and serves as a basic framework for building a quality culture more oriented towards sustainability and spirituality. This study concludes that the sustainable quality model based on Islamic values is very relevant to be applied in Islamic education to build superior institutional quality, integrity, and long-term orientation.